Attention and Consciousness: A Comment on Watzl's Structuring Mind. (6th September 2019) - O'Conaill, Donnchadh
Abstract : Sebastian Watzl has recently presented an attentional account of consciousness, on which it essentially involves subjects attending to the world as it appears to them. On this conception, consciousness has three structural features: unity, subjectivity and perspectivity. Watzl argues that the attentional account provides the best explanation of these features, and thus of consciousness conceived in this way. I outline problems with Watzl's proposed explanation of each of these structural features, and argue that these undermine his attentional theory of consciousness.